Effect Of The Aqueous Extract Of Nigella Sativa Seeds On Blood Serum Glucose, Cholesterol and Total Protein In · Alloxan-Induced Diabetic Rabbits - Al-Assede, Ekklass H.; Almzaien, Kahtan A. (The Iraqi Journal of Veterinary Medicine, 2003)
The effect of five weeks oral administration of the aqueous extract of Nigella Sativa Seeds (320 mg/kg body weight) on body weight, blood glucose, cholesterol and total protein (albumin and globulin) concentrations in alloxan induced diabetic rabbits was studied. Twenty-four mature male rabbits were randomly assigned into three groups of eight each. Diabetes was induced experimentally by intravenous injection of alloxan monohydrate (100 mg/kg body weight) into two groups; diabetic group (D), diabetic group which was orally administrated aqueous extract of Nigella Sativa seeds (DN) while the third group served as control(C). The results showed that the aqueous extract of Nigella Sativa seeds significantly reduced (P<0.01) the blood glucose and cholesterol concentrations in group (DN) and significantly increased the concentration of total protein (albumin and globulin), also inhibited the body weight reduction as compared with diabetic group (D) and the control (C). These results revealed the capability of the extract of Nigella Sativa seeds to ameliorate the biochemical changes induced by alloxan in diabetic rabbits.